Rotifers diversity in Kudla Dam near Umri Nanded, MS, India - Bhoyar VV (International Journal of Life Sciences, 2015)
The water quality and nutrients influence population of zooplanktons. The population observed in the distribution of zooplankton is due to abiotic factors (e.g. temperature, salinity DO and other dissolved ions), to biotic factors (e.g. nutrients). Many species of zooplanktons are limited by temperature, dissolved oxygen, salinity and other physico-chemical factors. Zooplanktons constitute an important link in food chain as (primary or secondary consumers) and serve as food for fishes directly or indirectly. Therefore any harm to these will be harmful to the fish populations. The occurrence of zooplankton depends upon its productivity, which is influenced by physico-chemical parameters and the level of nutrients in water. Hence the present study was carried out on kudla dam for a period of one year from Jun 2013 to May 2014. In the present study 19 species of Rotifers were found.